EDUCATION STATUS OF DIFFERENTLY ABLED PERSONS AT CUDDALORE DISTRICT, TAMIL NADU - Quran, S.Sathya; Quran, T.Sudha (International Journal of Psychosocial Rehabilitation, 2020)
Disability is considered a health problem or abnormality that is situated in an individual’s body or mind. According to a 2006 World Bank report 38 percent of differently abled children are compulsory goes to school in 6 to 13 aged but 75 percent differently abled children do not go to school. The major reason is lack of infrastructure facilities, trained teachers and other. A majority of the school personnel are not adequately trained to design and implement educational programmes for students with differently abled persons in schools. Although the Sarva Shiksha Abhiyan (SSA) envisages training of the teachers an analysis of the content merely covers issues of identification and management. Other facilities like building infrastructure ramps, play grounds, safe drinking water, separate toilets for boys and girls, special teachers. Even the number of teacher training courses is low, raising the number of effective teacher and ect. Government and Non-Government organisations continue the delivery of special education through grant-in –aids received from the government. The shortage of special education teachers is yet another challenge.